Penyelesaian Sengketa Tanah Wakaf Di Pengadilan Agama Surakarta - Nur Fajriyah, Astri; , Muh. Muhtarom S.H, M.H (2017)
This research aims to find out the cause of the dispute which in waqf and means of dispute resolution in waqf land in Surakarta Religious Court. The research method uses qualitative descriptive and the data gathering method uses interview to Panitera. The analysis data technique is descriptive data and inductive method. The results shows that the consideration of the judges of the waqf land dispute conducted by naẓīr, with written evidence and witnesses in the trial. Based the Law Number 41 in 2004 on waqf turns out there are other heirs who are sick with mental disorders. This shows that the requirements of waqf are cancelled. But in article 3 of Law Number 41 in 2004, it is mentioned that the waqf wich has been declared cannot be cancelled and is not against sharia. Then the object status of waqf will remain belonging to the Assegaf Mosque Surakarta. Keywords: The factors of cause disputes, consideration of the judge, the waqf of object status